Accuracy Optimization of anti-TB Drug Assays using Protein Evaluation in Calibration Curves during Pharmacokinetics Quality Assurance - Vallie, Sarfaraaz (Stellenbosch : Stellenbosch University, 2021)
Thesis (MMed)--Stellenbosch University, 2021.